2019
DOI: 10.3390/ijerph16183472
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Medical Trajectories of Stroke Patients Based on Group-Based Trajectory Modeling

Abstract: A high mortality rate is an issue with acute cerebrovascular disease (ACVD), as it often leads to a high medical expenditure, and in particular to high costs of treatment for emergency medical conditions and critical care. In this study, we used group-based trajectory modeling (GBTM) to study the characteristics of various groups of patients hospitalized with ACVD. In this research, the patient data were derived from the 1 million sampled cases in the National Health Insurance Research Database (NHIRD) in Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…First, we determined trajectories for the number of ED visits, hospitalizations, and outpatient visits separately using group-based trajectory modelling (GBTM), with extensions to account for non-random patient attrition due to death [22,45]. GBTM uses maximum likelihood to identify latent subgroups of individuals with similar trajectories for a variable and has been used to describe healthcare trajectories in other populations [46][47][48]. Details of the trajectory analyses are in the additional file.…”
Section: Discussionmentioning
confidence: 99%
“…First, we determined trajectories for the number of ED visits, hospitalizations, and outpatient visits separately using group-based trajectory modelling (GBTM), with extensions to account for non-random patient attrition due to death [22,45]. GBTM uses maximum likelihood to identify latent subgroups of individuals with similar trajectories for a variable and has been used to describe healthcare trajectories in other populations [46][47][48]. Details of the trajectory analyses are in the additional file.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the subgroup analysis of age and sex revealed that males and the elderly were more susceptible to stroke when exposed to low-level ambient NO 2 in the air. Similarly, a study about hospital admissions in China found that the elderly were more susceptible to stroke than the non-elderly [ 46 ]; another study found that male stroke patients were more susceptible to changes in NO 2 concentrations than female patients [ 47 ]. However, some previous studies found different results regarding the susceptibility of age to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…LSA is also employed to evaluate sequential and lag patterns of subjects with probabilities [14]. e Taiwan NHIRD contains longitudinal data, which have been used to support many epidemiology studies in different fields [1,2,8,9,22,23,25,26]. Recently, manifestations of the longitudinal data in the NHIRD were found.…”
Section: Discussionmentioning
confidence: 99%